Development of e-worksheet based on ExPRession learning model to train critical thinking skills - Nisa Fadilah; Kartini Herlina; Dimas Permadi; Wayan Suana (Universitas Ahmad Dahlan, 2023)
Education plays an important role in a country, so in the 21st century, education requires students to have skills that support them in facing global challenges. One of these skills is critical thinking skills. However, in learning, especially physics, critical thinking skills have not been widely applied. This Research aimed to develop e-worksheets based on external physical representation (ExPRession). This development research used the Design and Development Research (DDR) approach. The data analyzed are data from validity tests, namely language and design validity tests and Material and construct validity tests. In addition, the analysis data is also on the results of the practicality test consisting of readability, teacher perception, and student responses. The results of this study indicate that the results of the validity test for the media and design tests obtained a score of 3.50 with a very valid category, and for the material and construct validation test, a score of 3.38 was obtained with a very valid category. The practicality test results obtained a score of 83.8% in the very high practical category.